Distribution of mononucleotide repeats in bacterial chromosomes: A/T-tracts dominate on G/C-tracts - Sergey Sergeevich Kisselev; Vladislav Mikhailovich Komarov; Irina Stanislavovna Masulis; Olga Nikolaevna Ozoline (Компьютерные исследования и моделирование, 2010)
This study analyzes the abundance of mononucleotide tracts of different length in 342 eubacterial and 69 archaeal chromosomes. Despite the fact that the amount of analyzed repeats depends on nucleotide content, the predominance of poly(dA)n- and poly(dT)n-tracts on poly(dG)n- and poly(dC)n-tracts was found in 301 chromosomes (73 % of events), including 90 GC-rich chromosomes. In natural DNAs amount of A/T-tracts usually appeared to be two-fold higher than in randomized nucleotide sequences with the same AT/GC-content and length. Possible reasons of this asymmetry in distribution are discussed.